2013
DOI: 10.1002/jbm.a.34741
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and antibacterial properties of magnesium alloys in artificial urine for potential resorbable ureteral stent applications

Abstract: This article presents an investigation on the effectiveness of magnesium and its alloys as a novel class of antibacterial and biodegradable materials for ureteral stent applications. Magnesium is a lightweight and biodegradable metallic material with beneficial properties for use in medical devices. Ureteral stent is one such example of a medical device that is widely used to treat ureteral canal blockages clinically. The bacterial colony formation coupled with the encrustation on the stent surface from extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 51 publications
1
95
1
3
Order By: Relevance
“…Studies have found that several minutes after the ureteral stent was transplanted, salts and other substances in urine would deposit on the ureteral stent and create good conditions for the fix planting of bacteria. Urinary tract pathogens such as E. coli, Proteus, Staphylococcus, and Enterococcus would be fixed on the surface of the ureteral stent within 24 h, and form a bacterial biofilm [16,17]. The literature presents a variety of rates related to bacterial stent colonization, but there was no statistical difference between the patients with colonization and those without in terms of age, gender, and reason for stent insertion [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that several minutes after the ureteral stent was transplanted, salts and other substances in urine would deposit on the ureteral stent and create good conditions for the fix planting of bacteria. Urinary tract pathogens such as E. coli, Proteus, Staphylococcus, and Enterococcus would be fixed on the surface of the ureteral stent within 24 h, and form a bacterial biofilm [16,17]. The literature presents a variety of rates related to bacterial stent colonization, but there was no statistical difference between the patients with colonization and those without in terms of age, gender, and reason for stent insertion [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, artificial urine (AU) was used as an immersion solution. It was also noted in this study that human urine is much more variable in ionic composition between patients than blood or blood plasma [99]. Another application that could be considered is that of a Mg biliary stent, which has recently been investigated in vivo [100].…”
Section: Consideration For Other Bodily Fluidsmentioning
confidence: 75%
“…The work of Lock et al [99] provides a good example of this during their investigation of an Mg-Y alloy stent for use in the urine tract. In this study, artificial urine (AU) was used as an immersion solution.…”
Section: Consideration For Other Bodily Fluidsmentioning
confidence: 99%
“…Magnesium is promising for a wide range of biomedical applications, such as temporary tissue engineering scaffolds, fixation devices used in orthopedic, spinal and craniomaxillofacial surgeries, cardiovascular stents, and urological stents and catheters [1,2]. Generally, these devices only serve temporary functions in the body and should degrade and disappear when no longer needed.…”
Section: Magnesium As a Novel Biomaterials And Mechanism Of Degradationmentioning
confidence: 99%